Is Involvement in Religion Associated with Better Sleep Quality? - Krause, Neal M. (Pastoral psychology, 2017)
Findings from a considerable number of studies suggest that a wide range of psychosocial factors are associated with sleep quality. However, it is surprising to find that very few studies assess the relationship between religion and sleep quality. The purpose of this study is to examine the relationship between three key measures of religion and sleep quality. The data are from a recent nationwide survey of adults of all ages ( N = 1774). A conceptual model that contains the following core relationships was evaluated empirically: (1) people who go to church more frequently tend to receive more spiritual support from fellow church members (spiritual support is assistance that is provided with the explicit purpose of bolster the religious behaviors and beliefs of the recipient), (2) more spiritual support is associated with stronger God-mediated control beliefs (God-mediated control refers to the extent to which people believe God works with them to overcome challenges that arise in life), (3) people with a strong sense of God-mediated control will feel more hopeful about the future, and (4) individuals who are more hopeful will enjoy better quality sleep. Empirical support was found for each of these relationships.